PLS-SEM Approach to Second-order Factor of Entrepreneurial Orientation: The Moderating Role of Culture - Timothy Edward, Oswald (International Journal of Engineering and Technology, 2018)
Increasing challenges posed by globalization, liberalization, technological advances and explosive growth of information, make it critical for every firm to be entrepreneurial oriented. Past studies have shown that firms which display relatively high levels of innovation, risk-taking and proactive behaviour are known to have entrepreneurial orientation (EO), hence positively affect growth. This study investigates an integrated and complex relationship between entrepreneurship and performance by using partial least squares structural equation modelling (PLS-SEM). EO is tested with second-order factors comprised of innovativeness, proactiveness and risk taking propensity. In this survey, the consequences of EO to business performance of firms is examined in a sample of middle-level managers within the public listed companies in Malaysia. Consequently, the finding suggests that EO is in its initial stage; there is a significant correlation between the degree of EO and performance of firms; and cultural value is determinant in the degree of EO-performance relationship. Â Â